Regional resource management system - E. A. Ostapenko (Вестник университета, 2022)
The process of societal development is accompanied by profound social changes, which in turn cause new problems of social organisation. Among other things, organisational and management issues become very relevant. The above changes have a direct impact on the process of regional governance. The purpose of the study was to analyze regional development and determine the resource management system that is necessary for organizing effective management of the territory. The objectives of the study were to considerate issues of resource capacity management, identify and define the region’s basic resources. In the course of the study, methods of a general scientific and special nature were used: analysis, synthesis, abstraction, induction and deduction. Based on the results of the study, a resource capacity management structure is presented, and a development vector for the region is proposed and justified. Particular attention is paid to the importance and necessity of resource capacity development for the progressive development of the territory.